2021
DOI: 10.1016/j.cgh.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endoscopic Submucosal Dissection for Superficial Gastric Neoplasia in a Large Cohort in North America

Abstract: Background & Aims: Endoscopic submucosal dissection (ESD) is a widely accepted treatment option for superficial gastric neoplasia in Asia, but there are few data on outcomes of gastric ESD from North America. We aimed to evaluate the safety and efficacy of gastric ESD in North America. Methods:We analyzed data from 347 patients who underwent gastric ESD at 25 centers, from 2010 through 2019. We collected data on patient demographics, lesion characteristics, procedure details and related adverse events, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…Data on the efficacy of ESD (Table 1 ) are particularly robust in East Asian countries where the incidence of gastric cancer is significantly higher than it is in Western countries. Studies in Japan and South Korea have demonstrated en bloc resection in 95.3%-99.2%, complete resection in 87.7%-95.5% and curative resection in 81.7%-84.1%[ 90 - 94 ]. In Western countries however, data are more limited and results are variable.…”
Section: Endoscopic Treatment Of Gastric Neoplasiamentioning
confidence: 99%
“…Data on the efficacy of ESD (Table 1 ) are particularly robust in East Asian countries where the incidence of gastric cancer is significantly higher than it is in Western countries. Studies in Japan and South Korea have demonstrated en bloc resection in 95.3%-99.2%, complete resection in 87.7%-95.5% and curative resection in 81.7%-84.1%[ 90 - 94 ]. In Western countries however, data are more limited and results are variable.…”
Section: Endoscopic Treatment Of Gastric Neoplasiamentioning
confidence: 99%
“…ESD is an accepted treatment option for superficial gastric neoplasia in Asia, but there are little data on outcomes of gastric ESD from North America. 5,6 Ngamruengphong and colleagues 7 analyzed data from 347 patients who underwent gastric ESD at 25 North American centers. For the 277 patients with available follow-up data, the median interval between initial ESD and last clinical or endoscopic evaluation was 364 days.…”
Section: Efficacy Of Endoscopic Submucosal Dissection For Superficial Gastric Neoplasia In North Americamentioning
confidence: 99%
“…Equally as important, we need to raise awareness of endoscopic resection, specifically ESD, as the primary modality for most EGCs. At this point, multiple studies from the West have corroborated the feasibility and safety of ESD for the treatment of dysplastic lesions and EGCs when performed at centers with the appropriate expertise [16,17,19]. Our ultimate goal should be to provide patients with appropriate stage-specific therapy based on well-established criteria.…”
mentioning
confidence: 97%
“…Furthermore, it is worth noting that some studies from the West have suggested a higher rate of LNM in EGCs as compared to data originating from Asia, leading to the speculation of differences in biological aggressiveness of EGCs in the West [15]. Nonetheless, the discrepantly higher rate of LNM reported in the West as compared to Asia appears to be primarily driven by lesions meeting the expanded criteria, whereas EGCs within the absolute criteria have been associated with excellent outcomes and negligible risk for LNM [16,17]. Hence, not surprisingly, most of the endoscopic resections for EGCs reported in this study were for lesions meeting the absolute criteria; albeit it remains unclear how precise histopathological staging was obtained from the SEER database, particularly for the non-surgical specimens.…”
mentioning
confidence: 99%